White matter abnormalities of right hemisphere attention networks contribute to visual hallucinations in dementia with Lewy bodies. (June 2021) - Zorzi, Giovanni; Thiebaut de Schotten, Michel; Manara, Renzo; Bussè, Cinzia; Corbetta, Maurizio; Cagnin, Annachiara
Abstract: Objective: Functional alterations of the visual attention networks in a setting of impaired visual information processing have a role in the genesis of visual hallucinations (VH) in dementia with Lewy bodies (DLB). This multimodal MRI study aims at exploring structural and functional basis of VH. Methods: 23 DLB patients (10 with and 13 without VH) and 13 healthy controls were studied. They underwent MRI with T1-w sequences to measure cortical thickness, DTI for whole-brain and single tract microstructural properties and rs-fMRI of the default mode, dorsal and ventral attention, and visual networks. Results: In DLB with VH, whole-brain DTI revealed a lower fractional anisotropy and a greater mean diffusivity in the right frontal and temporo-parietal white matter tracts. Tracts dissection showed lower fractional anisotropy in the right inferior and superior (ventral part) longitudinal fasciculi (ILF and SLF) ( p  < .05, corrected), and greater mean diffusivity ( p  < .05). The extent of white matter microstructural alterations involving the right ILF and SLF correlated with the severity of VH ( r  = .55, p  < .01; r  = .42, p  < .05, respectively), and with performance in the visual attention task ( r  = −.56 and r  = −.61; p  < .01, respectively). Cortical thickness in the projection areas of the right SLF was significantly reduced ( p  < .05). Patients with VH also showed an altered functional connectivity in the ventral attention network, connected by the ventral portion of the SLF ( p  < .05). Conclusions: Our findings suggest that a combination of microstructural and functional alterations involving the attention networks in the right hemisphere may be important in the genesis of VH.